The Cerebellar Dopaminergic System - Flace, Paolo; Livrea, Paolo; Basile, Gianpaolo Antonio; Galletta, Diana; Bizzoca, Antonella; Gennarini, Gianfranco; Bertino, Salvatore; Branca, Jacopo Junio Valerio; Gulisano, Massimo; Bianconi, Simona; Bramanti, Alessia; Anastasi, Giuseppe (Frontiers in Systems Neuroscience, 2021)
In the central nervous system (CNS), dopamine (DA) is involved in motor and cognitive functions. Although the cerebellum is not been considered an elective dopaminergic region, studies attributed to it a critical role in dopamine deficit-related neurological and psychiatric disorders [e.g., Parkinson's disease (PD) and schizophrenia (SCZ)]. Data on the cerebellar dopaminergic neuronal system are still lacking. Nevertheless, biochemical studies detected in the mammalians cerebellum high dopamine levels, while chemical neuroanatomy studies revealed the presence of midbrain dopaminergic afferents to the cerebellum as well as wide distribution of the dopaminergic receptor subtypes (DRD1-DRD5). The present review summarizes the data on the cerebellar dopaminergic system including its involvement in associative and projective circuits. Furthermore, this study also briefly discusses the role of the cerebellar dopaminergic system in some neurologic and psychiatric disorders and suggests its potential involvement as a target in pharmacologic and non-pharmacologic treatments.